Lung stereotactic body radiotherapy after past ablative therapy: a single institution case series. (21st December 2018) - Wegner, Rodney E; Ahmed, Nissar; Hasan, Shaakir; Schumacher, Lana Y; Colonias, Athanasios
Aim: Non-small-cell lung cancer recurs locally 10–40% of the time after local therapy, presenting a therapeutic challenge given poor pulmonary reserve. Herein, we seek to evaluate the safety and efficacy of stereotactic body radiotherapy (SBRT) for retreatment of such patients.Methods: We identified and reviewed clinical outcomes in ten patients with recurrent non-small-cell lung cancer after past vicryl mesh brachytherapy.Results: Ten patients with a median age of 77 were treated to a median dose of 48 Gy in five fractions. Local control at 1 year was 88%. There was one distant failure at 29 months. There was no significant toxicity after SBRT.Conclusion: SBRT is safe and effective when used for re-irradiation after past ablative therapies.